-9x+15-2x=4-3x

Simple and best practice solution for -9x+15-2x=4-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+15-2x=4-3x equation:


Simplifying
-9x + 15 + -2x = 4 + -3x

Reorder the terms:
15 + -9x + -2x = 4 + -3x

Combine like terms: -9x + -2x = -11x
15 + -11x = 4 + -3x

Solving
15 + -11x = 4 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
15 + -11x + 3x = 4 + -3x + 3x

Combine like terms: -11x + 3x = -8x
15 + -8x = 4 + -3x + 3x

Combine like terms: -3x + 3x = 0
15 + -8x = 4 + 0
15 + -8x = 4

Add '-15' to each side of the equation.
15 + -15 + -8x = 4 + -15

Combine like terms: 15 + -15 = 0
0 + -8x = 4 + -15
-8x = 4 + -15

Combine like terms: 4 + -15 = -11
-8x = -11

Divide each side by '-8'.
x = 1.375

Simplifying
x = 1.375

See similar equations:

| y=9-x^2 | | 9/80-51/80= | | 34/43-(-12/34)= | | 19=-5-3X | | 3[9(x+4)+2(x+1)]= | | 8y+7=y-2 | | 81=-9y+6x | | x^3-4x=x^2-4 | | -9+6x=81 | | 63=9-9X | | 1.5(x+8)=7.8+0.9x | | 9[5+3(x+2)]= | | 5c^2=7c | | x^2+6z=-8 | | 3q+2=11 | | x^2+6z+8=0 | | 0.75x-3=0.5x+2 | | 4*8+9(3a+5)+8(2a+1)= | | y=x^2+4-5 | | 6x+1=4-x | | 4e^3x=1064 | | 16w^2+8w+1= | | 2x-5-4x=-3 | | logx=4.25 | | 5x+4x-20=62-(x+2) | | 5x+4(x-20)=62-x+2 | | 6-19=7x-8-6x | | 64a^2-81p^2= | | 14x-6y=30 | | 20x^2+13x-15=0 | | 1(3-x)=1-(x-2) | | 3x^2-x-48=-16 |

Equations solver categories